The Decoration of Braziers of the Catacomb Culture: Analysis of Composition - N V Panasyuk (RUDN Journal of World History, 2009)
The article is dedicated to the analysis of the decoration on censers of the catacomb culture, which existed in Eurasian steppes in the Middle Bronze Age. As censer was a ritual vessel it was used in the funeral rite. Censer usually was richly decorated. The analysis of the composition and of the system of decoration on censers allow clarifying the semantic of whole funeral rite, find the basis of religious views of the catacomb population.